2005
DOI: 10.1038/emm.2005.66
|View full text |Cite
|
Sign up to set email alerts
|

Role of γ-aminobutyric acid B (GABAB) receptors in the regulation of kainic acid-induced cell death in mouse hippocampus

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Moreover, activated astrocytes, mediators of the inflammatory response, promote the release of proinflammatory cytokines, which extends brain damage and contributes to behavioral changes and neuronal damage initiated by activation of KA receptors. Several studies in recent years have demonstrated that ERK signaling is activated in a model of KA-induced excitotoxicity (46,47). Furthermore, we also observed that C/EBP b upregulation in the hippocampus of DA-treated mice is disrupted by i.c.v.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, activated astrocytes, mediators of the inflammatory response, promote the release of proinflammatory cytokines, which extends brain damage and contributes to behavioral changes and neuronal damage initiated by activation of KA receptors. Several studies in recent years have demonstrated that ERK signaling is activated in a model of KA-induced excitotoxicity (46,47). Furthermore, we also observed that C/EBP b upregulation in the hippocampus of DA-treated mice is disrupted by i.c.v.…”
Section: Discussionsupporting
confidence: 60%
“…Kainic acid (KA) is a potent glutamate receptor agonist with selectivity towards non-N-methyl-D-aspartate (NMDA)-type glutamate receptors [3;4]. KA is well known for its ability to induce seizures within minutes of its administration and is followed by a delayed excitotoxic neuron death in the hippocampus several hours later, in part through an increase in intracellular calcium and activation of calcium-dependent neuron death pathways [5][6][7]. Both apoptotic and necrotic death of neurons Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] Upon binding to non-NMDA glutamate receptors, KA provokes depolarization of neurons followed by severe status epilepticus, neurodegeneration, memory loss, neuronal cell death. [39][40] The possible role of NMDA and non-NMDA receptors in the regulation of neurotoxic responses (lethality, memory loss, hippocampal cell death, signal transduction systems), stimulated by KA was discussed by Lee et al 41 The neuronal degeneration after KA administration is generally accepted to be associated with a depletion of ATP and accumulation of [Ca 2þ ] i.…”
Section: Discussionmentioning
confidence: 99%